Diagnostic accuracy of subjective dyspnoea in detecting hypoxaemia among outpatients with COVID-19: a retrospective cohort study - Berezin, Linor (BMJ Open, 2021)
OBJECTIVES: The majority of patients with mild-to-moderate COVID-19 can be managed using virtual care. Dyspnoea is challenging to assess remotely, and the accuracy of subjective dyspnoea measures in capturing hypoxaemia have not been formally evaluated for COVID-19. We explored the accuracy of subjective dyspnoea in diagnosing hypoxaemia in COVID-19 patients. METHODS: This is a retrospective cohort study of consecutive outpatients with COVID-19 who met criteria for home oxygen saturation monitoring at a university-affiliated acute care hospital in Toronto, Canada from 3 April 2020 to 13 September 2020. Dyspnoea measures were treated as diagnostic tests, and we determined their sensitivity (SN), specificity (SP), negative/positive predictive value (NPV/PPV) and positive/negative likelihood ratios (+LR/−LR) for detecting hypoxaemia. In the primary analysis, hypoxaemia was defined by oxygen saturation <95%; the diagnostic accuracy of subjective dyspnoea was also assessed across a range of oxygen saturation cutoffs from 92% to 97%. RESULTS: During the study period, 89/501 (17.8%) of patients met criteria for home oxygen saturation monitoring, and of these 17/89 (19.1%) were diagnosed with hypoxaemia. The presence/absence of dyspnoea had limited accuracy for diagnosing hypoxaemia, with SN 47% (95% CI 24% to 72%), SP 80% (95% CI 68% to 88%), NPV 86% (95% CI 75% to 93%), PPV 36% (95% CI 18% to 59%), +LR 2.4 (95% CI 1.2 to 4.7) and −LR 0.7 (95% CI 0.4 to 1.1). The SN of dyspnoea was 50% (95% CI 19% to 81%) when a cut-off of <92% was used to define hypoxaemia. A modified Medical Research Council dyspnoea score >1 (SP 98%, 95% CI 88% to 100%), Roth maximal count <12 (SP 100%, 95% CI 75% to 100%) and Roth counting time <8 s (SP 93%, 95% CI 66% to 100%) had high SP that could be used to rule in hypoxaemia, but displayed low SN (≤50%). CONCLUSIONS: Subjective dyspnoea measures have inadequate accuracy for ruling out hypoxaemia in high-risk patients with COVID-19. Safe home management of patients with COVID-19 should incorporate home oxygenation saturation monitoring.